EFEKTIVITAS DIKLAT TEKNIS SUBSTANTIF KEPALA MADRASAH ANGKATAN I DI KANTOR KEMENAG KABUPATEN BANJAR - Rahmadani (WIDYABORNEO, 2021)
The Substantive Technical Training for Madrasah Principals is based on regulatory requirements. In the legislation it has been explained that the headmaster is no longer an additional task but the headmaster is a teacher who is given the task to lead and manage the education unit. In this study only focuses on level 3 (behavior), which is looking at the work behavior of training participants after they return to their work environment, researchers will see the effectiveness of this training. Therefore, the authors assume that this research is very important to be done to see improvements in education and training programs both in the form of design and implementation. This study aims to determine the effectiveness of the substantive technical training of the head of the first generation madrasa at the Ministry of Religion in the Banjar Regency. Based on the results of the study using Kirkpatrick Level 3 (Behavior) evaluation conducted on the alumni of the Training and the perceptions of people around the alumni indicate that the Substantive Technical Training Head of Madrasah Force I Office of the Ministry of Religion in the Banjar Regency is in the GOOD category or at 88.82 . This acquisition is based on 5 aspects or perception, namely; alumni supervisors, alumni colleagues, alumni advisors officials, alumni customers (teachers & students) and the ability of the training participants themselves as alumni. Therefore this training can provide positive benefits to changes in performance (competence and commitment) of the madrasa head. Of the 5 competencies plus perception shows that after attending this training the alumni still need further guidance either by the madrasah supervisors, the Head of Academic Affairs and other staffing supervisors, especially in entrepreneurship and supervision competencies.